Effect of Increasing Running Cadence on Peak Impact Force in an Outdoor Environment - Taylor Musgjerd; Jacob Anason; Drew Rutherford; Thomas W Kernozek (North American Sports Medicine Institute, 2021)
# Background An estimated 56% of recreational runners sustain a running-related injury related to the high impact forces in running. Increasing step frequency (cadence) while maintaining a consistent speed has been shown to be an effective way to lower impact forces which may reduce injury risk. # Purpose To examine effects of increased cadence on peak impact force during running in an outdoor setting. It was hypothesized that as cadence increases, peak force would decrease. # Study Design Repeated measures, quasi-experimental # Methods Peak force and cadence measurements were collected from 15 recreational runners (8 females, 7 males) during two 2.4-mile outdoor runs. Peak force was measured using an insole-based load measuring device. Baseline session run was completed at participant's naturally preferred cadence and cadence session run was completed at a cadence targeted to be 10% greater than baseline. Pace was monitored with a GPS watch. Cadence was cued by an auditory metronome and measured with both GPS watch and insoles. Repeated-measures ANOVA's examined the differences in average peak force, GPS-reported cadence, and insole-reported cadence between mile 1 and mile 2, and across the two cadence conditions. # Results Cadence differences of 7.3% were observed between baseline and cadence sessions (p\<0.001). A concurrent decrease in average peak force of 5.6% was demonstrated during the cadence run (p\<0.05). Average cadences measured by GPS watch and insoles were found to be the same at both baseline (p=0.096) and during cadence (p=0.352) sessions. # Conclusion Increasing cadence by an average of 7% in an outdoor setting resulted in a decrease in peak force at two different time points during a 2.4-mile run. Furthermore, using a metronome for in-field cadence manipulation led to a change in cadence. This suggests that a metronome may be an effective tool to manipulate cadence for the purpose of decreasing peak impact force in an outdoor setting. # Level of evidence 3b